Pengaruh Kinerja Keuangan dengan Pendekatan Dupont System Terhadap Harga Saham Perusahaan Basic Material - Sari, Widya; Rahmazaniati, Linda; Vonna, Sari Maulida; Rahmadani, Ika; Putri, Cut Widy Aulia (Magister Ilmu Akuntansi Universitas Jambi, 2025)
The purpose of this study is to analyze how financial performance affects stock prices through the DuPont approach. At the close of the JCI on December 4, 2024, it can be seen that ten sectors experienced a decline in share price, with the Basic Materials sector being the most affected. At the first close of the JCI in 2025, the Basic Material sector still experienced the largest decline in stock price performance compared to other sectors. The population studied is Basic Material companies, especially the Other Metals & Minerals Sub-Sector, which is 16 companies, the sample taken is 8 companies using purposive sampling method. For analysis, the method used is panel data regression. Separately, Dupont's NPM, TATO, and ROE have no influence. EM has a significant influence. Overall, Dupont's NPM, TATO, EM, and ROE variables have an influence on Stock Prices.